Improvement of asthenia in patients with systemic lupus erythematosus (SLE) and undifferentiated connective tissue diseases (UCTD) with the use of a SOD-enriched whey protein formula - Rossi, R.; Catania, G.; Corsetti et al., M.T. (Progress in Nutrition, 2011)
Summary In this work we report the results of our study on fatigue in a cohort of 100 patients with systemic lupus erythematosus (SLE) and undifferentiated connective tissue disease (UCTD). We evaluated the efficacy on fatigue, of a preparation of way proteins characterized by high content of cysteine and cystine (ProtherTM SOD). The results showed that this preparation is effective in controlling fatigue in this group of patients. Miglioramento dell’astenia in pazienti affetti da lupus ertematoso sistemico e da connettivite indifferenziata con l’impiego di una formulazione di proteine da siero di latte arricchita con superossido-dimutasi Riassunto In questo articolo riportiamo i risultati del nostro studio, condotto su 100 pazienti affetti da lupus eritematoso sistemico (LES) e da connettivite indifferenziata, con lo scopo di valutare l’efficacia, sull’astenia, di una preparazione a base di proteine da siero di latte, ad elevato contenuto di cisteina e di cistina (ProtherTM SOD). I risultati ottenuti dimostrano che la formulazione è efficace nel controllo di tale sintomo nei pazienti presi in considerazione.